Recent changes in distribution and relative abundance of cetaceans in the Norwegian Sea and their relationship with potential prey - Nøttestad, Leif; Krafft, Bjørn A.; Anthonypillai, Valantine; Bernasconi, Matteo; Langård, Lise; Mørk, Herdis L.; Fernö, Anders (Frontiers in Ecology and Evolution, 2015)
This study aimed to assess possible shifts in distributional patterns of cetaceans residing in the Norwegian Sea, and if possible relate the distribution to their feeding ecology during the summer seasons of 2009, 2010 and 2012. During this same period, historically large abundances in the order of 15 million tonnes pelagic planktivorous fish such as Norwegian spring-spawning herring (Clupea harengus), northeast Atlantic mackerel (Scomber scombrus) and blue whiting (Micromesistius poutassou), have been reported feeding in the Norwegian Sea during the summer. There is also observed elevated average surface temperatures and a reduction in zooplankton biomasses. Such changes might influence species composition, distribution patterns and feeding preferences of cetaceans residing the region. Our results show higher densities of toothed whales, killer whales (Orcinus orca) and pilot whales (Globicephala melas), than the previous norm for these waters. Baleen whales, such as minke whales (Balaenoptera acutorostrata) and fin whales (Balaenoptera physalus), which is often associated with zooplankton, displayed a distribution overlap with pelagic fish abundances. Humpback whales (Megaptera novaeangliae) were observed in low numbers, indicating shift in habitat preference, compared to sighting data collected only few years earlier. Our study illustrate that both small and large cetaceans that reside in the Norwegian Sea have the capability to rapidly perform shifts in distribution and abundance patterns dependent of the access to different types and behaviour of prey species.